The development of 177Lu-DOTA-CC-PSMA following a unified "Click Chemistry" protocol of synthesizing metal nuclide-conjugated radiopharmaceuticals - Xiaobei Zheng; Shuai Xue; Zhongqi Zhao; Shuxin Jin; Shuhua He; Lina Jia; Zheng Li; Christian Vanhove; Filip De Vos; Zijun Kuang; Tiantian Wang; Sara Neyt; et al. (SpringerOpen, 2024)
Abstract Background Currently, the synthesis pathway of metal nuclide-labeled radiopharmaceuticals is mainly divided into two steps: first, connecting the chelator with the target molecule, and second, labeling the metal nuclide to the chelator. However, the second step of the reaction to label the metal nuclide requires high temperature (90-100 °C), which tends to denature and inactivate the target molecule, leading to loss of biological activities, especially the targeting ability. A feasible solution may be the click chemistry labeling method, which consists of reacting a metal nuclide with a chelating agent to generate an intermediate and then synthesizing a radiopharmaceutical agent via the click chemistry intermediate and the target molecule-alkyne compound. In this study, through the click chemistry of 177Lu-DOTA-N3 with prostate-specific membrane antigen (PSMA)-alkyne compound, 177Lu-labeled PSMA-targeted molecular probe was synthesized and evaluated for its potential to be cleared from the bloodstream and rapidly distributed to tissues and organs, achieving a high target/non-target ratio. 177Lu-PSMA-617 was utilized as an analogue for comparison in terms of synthesizing efficiency and PSMA-targeting ability. Results A novel 177Lu-labeled PSMA radioligand was successfully synthesized through the click chemistry of 177Lu-DOTA-N3 with PSMA-alkyne compound, and abbreviated as 177Lu-DOTA-CC-PSMA, achieving a radiochemical yield of 77.07% ± 0.03% (n = 6) and a radiochemical purity of 97.62% ± 1.49% (n = 6) when purified by SepPak C18 column. Notably, 177Lu-DOTA-CC-PSMA was characterized as a hydrophilic compound that exhibited stability at room temperature and commendable pharmacokinetic properties, such as the superior uptake (19.75 ± 3.02%ID/g at 0.5 h) and retention (9.14 ± 3.16%ID/g at 24 h) within xenografts of 22Rv1 tumor-bearing mice. SPECT/CT imaging indicated that radioactivity in both kidneys and bladder was essentially eliminated after 24 h, while 177Lu-DOTA-CC-PSMA was further enriched and retained in PSMA-expressing tumors, resulting in the high target/non-target ratio. Conclusion This study demonstrated the potential of click chemistry to unify the synthesis of metal radiopharmaceuticals, and 177Lu-DOTA-CC-PSMA was found for rapid clearance and appropriate chemical stability as a PSMA-targeted radioligand.